Social role of microfinance institutions in poverty eradication: evidence from ASEAN-5 countries - Zainal, Nurazilah; Md Nassir, Annuar; Kamarudin, F.; Hook, L. S.; Sufian, Fadzlan; Hussain, Hafezali Iqbal (Primrose Hall Publishing Group, 2019)
Banking institutions have witnessed the failure of poverty reduction due to high risk service for poor people. Microfinance institutions (MFIs) were developed to provide financial services for low income households. In the drive to supply continuous financial services for the poor, performance of the MFIs has been one of the crucial aspects that needs consideration. The MFIs began with a social goal aim of poverty reduction. However, the commercialization of the MFIs has resulted in them becoming financially independent as they are funded by a previous government. Today the MFIs need to retain the social role, to eradicate poverty whilst at the same time they must strive to sustain long term operation. Are the MFIs still able to sustain their social goals when they also need to focus on financial sustainability? This study proposes to determine the level of social efficiency among MFIs in ASEAN 5 countries as the first objective. Secondly it will examine the impact firm characteristics that internally influence the social efficiency of the MFIs. The data consists of 168 MFIs from Southeast Asia that covers five countries from the year 2011 to 2017. The first stage of analysis to identify the level of social efficiency by using non parametric Data Envelopment Analysis (DEA) approach. The second stage of analysis is to examine the impact of firm characteristics to influence the social efficiency by applying Multivariate Panel Regression Analysis (MPRA) as an estimation method. The findings reveal the MFIs in ASEAN 5 countries have a lower social efficiency. This indicates the MFIs in ASEAN 5 countries has traded their original mission of poverty reduction to focus more on achieving financial sustainability for long term viability.